Efektifitas Dakwah Kiai Melalui Majalah (Studi Atas Efek Tulisan Kiai Bagi Santriwati di Pondok Pesantren Al-Amien Prenduan) - Iwan Kuswandi (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2016)
Dakwah (preaching) through writing can make scholars immortal. In addition to preach orally, Muslim scholars in this regard kiai of Islamic boarding school, should also be able to preach through writing. Doing these two methods could be considered as the perfect preaching of kiai. In terms of preaching through writing, kiai not only had to write a book, as classical scholars did. Nowadays, kiai should be able to do preach through mass communication media, such as writing in the magazine. This paper finds out that mostly the papers magazine of kiai are in accordance with the capacity of knowledge and interests for its readers (Santri-santriwati). Surely, there are some reasons for delight readers on the writings of kiai in magazines. One of them was due to see capacity knowledge of kiai. As for their internal motivations, can add their new knowledge by reading the writings of kiai in magazines. Even, it turns out that the writings of kiai also give influence to its readers, such as can motivate them to become authors.